An efficient approach for data-duplication detection based on RDBMS - Chanhom K. (2014)
Data-duplication is one of the most important issues in the context of information system management. Instead of storing a single real-world object as an entity in an information system, the duplication, storing more than one entity representing a single object, can be occurred. This problem can decrease the quality of service of information systems. In this paper, we propose an efficient approach to detect the duplication based on the RDBMS foundation. Our approach is based on the assumption that the data to be processed have been stored in the RDBMS at the first place. Thus, the proposed approach does not require the data to be imported/exported from the storage. Also, such approach will benefit from the query optimizer of the RDBMS. The experiment results on the TPC-H dataset have been presented to validate such proposed work. © 2011 IEEE.